Adoption of Bt Cotton and its Impact - A Case Study of Haveri District, Karnataka - Yatnalli, C. S. (Indian Journal of Marketing, 2010)
Indian agriculture witnessed technological innovation in the mid sixties, which is termed as ’Green Revolution’. The discovery of High Yielding Varieties (HYV’s), the package of practice for realizing their potential, the mechanization of agriculture involving the development of machinery system for irrigation, tillage, harvesting, threshing etc., are regarded as technological innovations in agriculture. Now withstanding the above constraints, agriculture in India has undergone changes of one kind or the other, mostly in the positive direction during the past three decades. It was the Green Revolution in the seventies followed by White Revolution in the eighties. More recently, the country is witnessing the ’Blue and Yellow revolutions’. India, on account of its geographical location, soil conditions and climate, possesses optimum conditions for the cultivation of cotton. Though cotton is grown in India from times immemorial, India’s story of progress in the production of cotton, particularly since her independence, has been spectacular. With 86 Million hectares, largest acreage in the world under cultivation of cotton, India is the largest producer of cotton in the world after China and USA. However, yield is one of the lowest in the world, less than 300 kg/ha as against world average of 608 kg /ha. Only one third of cotton area is irrigated while two-thirds is rain fed. India produces all types of cotton - short staple, medium staple, long staple and also extra staple cotton. Cotton varieties in India are many. However, 20-25 varieties only accounted for 97 percent of the cotton produced and 80-100 varieties make up the remaining three percent. Cotton is one of the important cash crops of the country. It occupies a significant place in the agricultural and industrial (textile) economy of the country. Nearly 15 million farmers spread out in over 10 states are dependent on cotton cultivation for their livelihood. The cotton area in India shot up to 90 lakh hectares during 2006-07. Next season, it was projected at 95 lakh hectares; China had 57 lakh hectares under cotton, while US had 42 lakh hectares two years ago. As a result, India in fact tops the area under cotton cultivation for the crop year 20073. No other country has improved the yield as India. Yield has gone up because of better crop management practices, reduction of pesticides and other initiatives, said Mr. Nair, Secretary General of Cotton Federation of Indian Textile Industry.